2009
DOI: 10.1210/jc.2009-0058
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc-α2-Glycoprotein Correlates with Adiposity, Triglycerides, and the Key Components of the Metabolic Syndrome in Chinese Subjects

Abstract: ZAG might be involved in the pathogenesis of obesity-related metabolic disorders in humans and thus warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
88
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(106 citation statements)
references
References 34 publications
16
88
1
1
Order By: Relevance
“…Zinc-α-2 glycoprotein presented higher values only in obese individuals who had not been subjected to bariatric surgery. In another study, higher serum levels of this protein were found for obese individuals than for those with normal weight [45]. Consequently, the increased expression of this protein in the saliva of obese individuals, observed in our study, may reflect higher levels of the protein in the blood.…”
Section: Discussionsupporting
confidence: 60%
“…Zinc-α-2 glycoprotein presented higher values only in obese individuals who had not been subjected to bariatric surgery. In another study, higher serum levels of this protein were found for obese individuals than for those with normal weight [45]. Consequently, the increased expression of this protein in the saliva of obese individuals, observed in our study, may reflect higher levels of the protein in the blood.…”
Section: Discussionsupporting
confidence: 60%
“…However, the data on serum ZAG levels in relation to obesity are inconsistent, being reported as decreased, 52,55 unchanged 57 or increased. 58 Circulating ZAG levels have been shown to be negatively 56 or positively 58 correlated with insulin and the insulin resistance indices. It is possible that adipose tissue-derived ZAG is more important locally through its autocrine/paracrine actions.…”
Section: Zag Expression and Body Fat Massmentioning
confidence: 99%
“…ZAG has been shown to act as a lipid-mobilizing factor (6). Treatment with ZAG stimulates lipolysis in isolated mouse and human adipocytes, and it selectively reduces body fat in both with adiposity, triglycerides (TG), and the key components of metabolic syndrome (8). Additionally, ZAG expression and protein levels have been reported to be down-regulated in subcutaneous and visceral adipose tissue of obese men and women in comparison with the lean controls (9).…”
Section: Introductionmentioning
confidence: 99%